Transactions of Exchanging Intangible Objects With Tangible Objects Are Islamic Law on That Application "ituloh" - Wadi, Fajrul; Hendri; Na’ali, Basri (NUSANTARA: Journal Of Law Studies, 2023)
This study describes the description of Islamic law regarding transactions of exchanging points for money in the application by the way the user presses the point withdrawal button and selects the desired amount of exchange and merchandising. This type of research is qualitative-empirical, with data collection techniques in the form of observation, interviews, and documentation; and data analysis techniques used are data reduction, presentation, and conclusion. The study's results indicate that in the exchanging of coins for money and merchandise in its application, sighat (transaction) is not directly stated between the parties, but it appears in the deed. The transaction mechanism is described as exchanging intangible goods in the form of coins. The seller makes an exchange by pressing the withdraw money/balance button, and the buyer gives the money sent to the E-wallet Fund Balance and mercerize. In Islamic law, exchanging points for money in the application is allowed because it fulfils the conditions and pillars of buying and selling, illustrated by deeds. Coins are earned by doing missions watching 15-30 minute long videos, and inviting new users. Earning points using a sale and purchase agreement based on the Ju'alah concept remains valid if the commission/reward given is in the form of goods and not money so that the points become valid objects/goods in a sale and purchase transaction. Ijab qobul in transactions is illustrated based on the willingness between parties to exchange points for money. In addition, points exchange transactions for money are also mutually beneficial for both parties.